2012
DOI: 10.1080/15374416.2012.675571
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Effects of Exposure to Violence on Posttraumatic Stress in Palestinian and Israeli Youth

Abstract: Objective We examine cumulative and prospective effects of exposure to conflict and violence across four contexts (ethnic-political, community, family, school) on post-traumatic stress (PTS) symptoms in Palestinian and Israeli youth. Method Interviews were conducted with 600 Palestinian and 901 Israeli (Jewish and Arab) children (ages 8, 11, and 14) and their parents once a year for three consecutive years. Results Palestinian children, males, and older youth were generally at greatest risk for exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 28 publications
4
57
0
4
Order By: Relevance
“…Each of the seven studies found a positive relationship between political violence exposure to and increased risk of PTSD in both populations (Al-Krenawi et al, 2009; Dubow, Boxer, et al, 2012; Dubow, Huesmann, et al, 2012; Hamama-Raz, Solomon, Cohen, & Laufer, 2008; Lavi & Solomon, 2005; Pat-Horenczyk et al, 2009; Schiff et al, 2012). …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Each of the seven studies found a positive relationship between political violence exposure to and increased risk of PTSD in both populations (Al-Krenawi et al, 2009; Dubow, Boxer, et al, 2012; Dubow, Huesmann, et al, 2012; Hamama-Raz, Solomon, Cohen, & Laufer, 2008; Lavi & Solomon, 2005; Pat-Horenczyk et al, 2009; Schiff et al, 2012). …”
Section: Resultsmentioning
confidence: 98%
“…Three studies examined the importance of school, peer and family relations as protective factors against PTSD symptom severity (Elbedour et al, 2007; Punamäki et al, 2001; Thabet et al, 2009). Three studies showed that school and family violence was associated with greater PTSD symptoms (Al-Krenawi, Graham, & Sehwail, 2007; Dubow et al, 2009; Dubow, Boxer, et al, 2012). One study noted that higher maternal love and caring was associated with PTSD symptom severity (Punamäki et al, 2001) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies highlight the risk of poor mental health outcomes among children growing up amidst military and political violence, particularly within the diagnostic category of posttraumatic stress disorder (PTSD) (Barber & Schluterman, 2009a, 2009bDubow, Huesmann, et al, 2012;Kohrt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the Occupied Palestinian Territories and Jerusalem, a cohort of 600 children in 3 initial age cohorts (8,11, and 14 years old) has been followed over 3 years to study the relationship of exposure to political conflict with violence in the family, community, and school to posttraumatic stress (PTS) symptoms and aggressive behavior. 4,5 Findings have documented both the cumulative effects of exposure to political violence and the need to examine and understand the full spectrum of violence exposure and the dynamics underway between community and familial violence and stress that shape mental health and adjustment in war-affected youth. In Northern Ireland, a study of 700 mother-child dyads in both Protestant and Catholic neighborhoods found that sectarian community violence was associated with elevated family conflict as well as children's reduced security about multiple aspects of their social environment (family, parent-child relations, and community).…”
Section: What This Study Addsmentioning
confidence: 99%